Integrated carbon capture and conversion: A review on C2+ product mechanisms and mechanism-guided strategies - Jana, Asmita; Snyder, Seth W.; Crumlin, Ethan J.; Qian, Jin (Frontiers in Chemistry, 2023)
The need to reduce atmospheric CO2 concentrations necessitates CO2 capture technologies for conversion into stable products or long-term storage. A single pot solution that simultaneously captures and converts CO2 could minimize additional costs and energy demands associated with CO2 transport, compression, and transient storage. While a variety of reduction products exist, currently, only conversion to C2+ products including ethanol and ethylene are economically advantageous. Cu-based catalysts have the best-known performance for CO2 electroreduction to C2+ products. Metal Organic Frameworks (MOFs) are touted for their carbon capture capacity. Thus, integrated Cu-based MOFs could be an ideal candidate for the one-pot capture and conversion. In this paper, we review Cu-based MOFs and MOF derivatives that have been used to synthesize C2+ products with the objective of understanding the mechanisms that enable synergistic capture and conversion. Furthermore, we discuss strategies based on the mechanistic insights that can be used to further enhance production. Finally, we discuss some of the challenges hindering widespread use of Cu-based MOFs and MOF derivatives along with possible solutions to overcome the challenges.